(untitled) (Journal of Education and Development, 2022)
As one of the basic responsibilities of a modern university, scientific research integrates knowledge discovery, talent training and the inheritance of scientific spirit, making it an inherent requirement for running a socialist university well and cultivating new talents who are responsible for national rejuvenation in the era. Ideological and political workers in colleges and universities have their unique advantages in grasping the ideological characteristics and psychological development characteristics of college students and guaranteeing the construction of study style. Therefore, it is of great significance to explore the promoting role of ideological and political workers in colleges and universities in scientific research and education.